Politik Hukum Sistem Perencanaan Pembangunan Nasional Sebagai Pedoman Dalam Penyelenggaraan Perencanaan Pembangunan Daerah - Ferika Nurfransiska; Redyana Lutfianidha; Maryuliyanto; Wahyu Mustariyanto (Judge : Jurnal Hukum, 2025)
This article aims to find out the Implementation of National Development Planning and Regional Development Planning. And to find out the Hierarchy of Legislation in Indonesia that regulates the Establishment of the National Development Planning System. This article uses a normative legal research method, namely by conducting a literature study of primary legal materials, namely the Law approach. In addition to primary legal materials, this study also uses secondary legal materials consisting of literature, scientific journals, and expert opinions related to the legal politics of the national development planning system in the implementation of regional development planning and the Hierarchy of Legislation in Indonesia that regulates the Establishment of the National Development Planning System. The results of the study indicate that national development is carried out continuously with the hope of improving the standard of living and welfare of the Indonesian people. National development planning and regional development planning are a process of compiling stages of activities that involve various stakeholder elements in it, in order to utilize and allocate existing resources in order to improve social welfare in a regional/regional environment within a certain period of time. The existence of various types of laws and regulations in the Republic of Indonesia in a hierarchical structure also results in differences in terms of the function and content of the various types of laws and regulations. Based on this, the function of each type of law and regulation must be in accordance with its hierarchy. It must be applied consistently in each existing law and regulation, which is then described in the Law in the Government Regulation as an implementing regulation, including higher regulations with content that delegates the formation of lower implementing regulations, or regulations that are formed as guidelines in compiling regulations at the same level or below.